Surgical Management of Stress Urinary Incontinence - Sharifi-Aghdas, Farzaneh (Urology Journal, 2009)
Introduction: This review evaluates the most recent knowledge regarding surgical management of stress urinary incontinence. Materials and Methods: A comprehensive MEDLINE search was performed, limited to those articles published from 1995 to 2005; 470 articles were reviewed. The most relevant of which were considered, and additional ones were selected by reviewing these studies’ bibliographies. Overall, 53 articles were selected and used in this study. Results: Few randomized controlled trials have been done. The best results of retropubic procedures are seen when the intrinsic urethral sphincter is competent and its effectiveness is sustained in the long term. A laparoscopic approach, although less popular and with a lower short-term cure rate, is an alternative. Sling surgeries can be the first-line treatment for all types of stress urinary incontinence. Autologous grafts are still considered the gold standard, but synthetic materials such as tension-free tape have comparable results with standard open retropubic procedures. Still, long-term–cure and complication rates have not yet been elucidated. Using urethral bulking agents is the least invasive approach, applicable in both intrinsic sphincter deficiency and urethral hypermobility. However, it has a poor long-term outcome and necessitates repeat injections. Conclusion: Long-term data suggest that Burch colposuspension and sling procedures produce similar objective cure rates. New synthetic suburethral slings such as tension-free vaginal tape have gained popularity in recent years. Complications of traditional and newer suburethral slings are declining, but they still occur and often are associated with serious morbidity. New therapies should be studied in randomized clinical trials and compared with conventional approaches.